The Websites Of Iraqi Public Universities On The Internet And Ways To Develop Them By Proposing Special Criteria For Their Evaluation - et. al., Dr. Thanaa Lilo Abbas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to evaluate the websites of Iraqi government universities and to identify the reality of the websites of Iraqi government universities through several suggested criteria, as (5) university sites representing Iraqi public universities were chosen, and the researcher relied on the descriptive approach in surveying the websites of government universities The Iraqi evaluation process revealed that there is weakness in some sites in the process of applying the standards and the research identified the places of failures in the analysis tables and made a set of recommendations that it deems appropriate to address these failures and direct the attention of Iraqi government universities to pay attention to their sites and benefit from the proposed criteria in the design process Their locations.